Ultrafast hardening concrete repairing material and preparation and construction method thereof
By using ultra-fast hard concrete restoration materials, the damage problem of cement concrete restoration materials under load and environment is solved, and the repair effect of rapid condensation, early high strength and strong weather resistance is achieved, reducing construction complexity and cost. In order to restore concrete pavement and other structures.
Patent Information
- Application Number
- CN202411477809.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-14
AI Technical Summary
Existing cement concrete restoration materials are prone to damage under load and environment, resulting in traffic problems, and have poor repair quality, high cost, short durability, and are easily affected by harsh environments, complex construction and short service life.
Use ultra-fast hard concrete restoration materials, including high-Belite sulfaluminate cement, fine aggregate, polycarboxylic acid water reducer, lithium carbonate accelerator, sodium pre-solution retarder, fiber, corrosion-resistant materials, blending The material and adhesive are mixed with powder mixer, mixed with water and then applied to the surface to be repaired, and then repaired after curing.
It achieves rapid condensation, early high strength, strong weather resistance, frost resistance, seepage resistance, good corrosion resistance, high compressive and flexural strength, convenient construction and good fluidity, reduces labor costs, and is environmentally friendly, non-toxic and odorless. Suitable for restoring concrete pavement and other structures.
Smart Images

Figure BDA0005096576730000101 
Figure BDA0005096576730000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete repair materials, and in particular to an ultra-fast hardening concrete repair material and a preparation and construction method thereof. Background Art
[0002] With the rapid development of my country's national economy, the construction of various highways, bridges, and municipal engineering projects has been rapid. Among them, the proportion of cement concrete pavement has increased significantly. A large number of concrete-based roads have been used for a long time or have been crushed by heavy vehicles. Under the repeated action of loads and the natural environment, such as freeze-thaw cycles, salt freezing, carbonization and other factors, as well as the combined action of many factors such as design, construction, and maintenance, cement concrete pavements will inevitably suffer various damages during use, such as cracks, potholes, and cracks, which affect the speed and quality of traffic and cause traffic problems. In order to minimize traffic problems, these damaged roads must be repaired in a timely manner.
[0003] Currently, cement concrete is used for repair. However, the formula design of cement concrete is not reasonable and scientific, and the cost is high. The repair quality is poor, and various technical performances are poor, resulting in repeated repairs and waste of materials and labor costs. After the pits are repaired, the strength is low and the durability is poor, which wastes a lot of raw materials, increases the workload of the construction unit, and causes huge economic losses. It is easily affected by harsh environments such as low temperature, rain and snow. The implementation process is complicated, the service life is short, and the stability is poor. Summary of the invention
[0004] In order to solve the above problems, the present invention provides an ultra-fast hardening concrete repair material and a preparation and construction method thereof.
[0005] The above technical objectives of the present invention are achieved through the following technical solutions:
[0006] An ultra-fast hardening concrete repair material comprises the following raw materials in parts by weight:
[0007] 400-480 parts of high-belite sulphoaluminate cement, 470-520 parts of fine aggregate, 2-4 parts of water reducer, 0.3-1.5 parts of accelerator, 0.3-1.0 parts of retarder, 1-2 parts of fiber, 0.5-1.0 parts of defoamer, 4-6 parts of masterbatch, 10-13 parts of corrosion-resistant material, 15-20 parts of adhesive, 40-60 parts of color powder or color paste, 0.5-1.0 parts of water retaining agent, and the rest are admixtures;
[0008] The admixture includes one or more of fly ash, heavy calcium powder, talcum powder, bauxite powder, and silica ash, wherein the fly ash is 50-100 parts, the heavy calcium powder is 50-100 parts, the talcum powder is 10-12 parts, the bauxite powder is 8-10 parts, and the silica ash is 15-25 parts.
[0009] Color powder or color paste is used for decorative purposes. It is added according to the product instructions based on the desired color depth and color requirements. The amount of color paste should be adjusted according to its concentration and color effect.
[0010] Furthermore, the water reducing agent is polycarboxylic acid, and its water reducing rate can reach 25%-35%, which can effectively reduce the water-cement ratio and improve the strength and working performance of concrete.
[0011] Furthermore, the coagulant is lithium carbonate, which can effectively shorten the coagulation time.
[0012] Furthermore, the retarder includes one or more of sodium tartrate, sodium citrate and tartaric acid, which can prolong the setting time.
[0013] Furthermore, the fibers are polypropylene fibers and / or steel fibers.
[0014] Furthermore, the corrosion-resistant material includes acid-resistant powder.
[0015] Furthermore, the adhesive is rubber powder.
[0016] Furthermore, the water retaining agent is cellulose, which can reduce the bleeding of concrete and improve the water retention performance.
[0017] The construction method of the above-mentioned ultra-fast hardening concrete repair material comprises the following steps:
[0018] S1. Weigh the above raw materials and set aside;
[0019] S2. Place the raw materials in S1 in a powder mixer and mix them evenly to obtain a repair material.
[0020] The method for using the above-mentioned ultra-fast hardening concrete repair material comprises the following steps:
[0021] S1. Clean the concrete surface to be repaired;
[0022] S2. Mix the above repair materials with water and mix them evenly at the construction site, then apply them on the concrete surface to be repaired;
[0023] S3. After solidification, the repair of the concrete is completed.
[0024] In summary, the present invention has the following beneficial effects:
[0025] High Belite cement, also known as low-heat cement or high-performance low-heat Portland cement, is a type of cement with special properties. It uses dicalcium silicate as the dominant mineral (greater than 50%) and has a low aluminum content, which breaks through the composition design of general Portland cement clinker with tricalcium silicate as the dominant mineral. The low hydration heat property enables it to effectively control the generation of temperature cracks in large-volume concrete construction; the high late strength ensures the long-term stability and durability of the concrete structure; the low shrinkage rate effectively reduces the risk of concrete cracking; and the high resistance to sulfate erosion enables it to maintain excellent performance in harsh environments. In addition, high Belite cement also exhibits good wear resistance and is suitable for various engineering occasions that require high wear resistance. Not only that, high Belite cement consumes less energy during the production process and emits relatively less harmful gases, which not only reduces production costs, but also makes it an environmentally friendly cement that meets the current era of green development requirements.
[0026] Fibers can control the further development of cracks in the matrix concrete, thereby improving crack resistance. Due to the high tensile strength and elongation of fibers, the tensile, bending, impact strength, elongation and toughness of concrete are improved.
[0027] Corrosion-resistant materials are materials that can form a protective layer to prevent corrosion on the concrete surface. Generally speaking, corrosion-resistant materials can be divided into two types: organic coatings and inorganic coatings. Organic coatings mainly refer to polymer coatings, such as epoxy resin coatings, polyurethane coatings, etc. Inorganic coatings mainly refer to silicate coatings, such as potassium silicate coatings, sodium silicate coatings, etc. These coatings can form a protective layer on the concrete surface to prevent the entry of external acidic substances, thereby improving the corrosion resistance of concrete.
[0028] Admixtures refer to one or more non-cement mineral materials added to cement, such as slag powder, wollastonite, fly ash, etc. The compounds such as calcium oxide and magnesium oxide contained in these admixtures can react with compounds such as calcium hydroxide and calcium sulfate in cement to form new compounds, thereby reducing the content of alkaline substances in concrete, reducing the alkalinity of concrete, and improving the corrosion resistance of concrete.
[0029] The functions of fly ash in concrete include: lubrication, water saving, and improving the overall performance of concrete; filling, adjusting particle grading, and improving concrete density; chemical action, gelling effect, and further improving concrete performance.
[0030] The main uses of heavy calcium powder in concrete include: controlling cement setting time: heavy calcium can promote the early setting of cement, improve the early strength and initial hardening rate of cement, and facilitate the rapid progress of construction; improving compressive strength: heavy calcium can improve the compressive strength of cement, improve the mechanical properties of cement, and make concrete hard and wear-resistant.
[0031] Talc has excellent physical and chemical properties such as lubricity, fire resistance, acid resistance, insulation, high melting point, chemical inactivity, good hiding power, softness, good gloss, strong adsorption, etc. Since the crystal structure of talc is layered, it has a tendency to split into scales and special lubricity. Features: increase the stability of product shape, increase tensile strength, shear strength, flexural strength, pressure strength, reduce deformation, elongation, thermal expansion coefficient, high whiteness, uniform particle size, strong dispersion, etc.
[0032] Bauxite powder is one of the important raw materials for producing special cements such as fireproof cement, acid-resistant cement, and sulfate cement. These cements have excellent fire resistance, acid resistance, and chemical corrosion resistance, and can improve the strength and density of cement gel, making the cement have better crack resistance and durability after hardening. At the same time, it can adjust the chemical composition and microstructure of cement, thereby improving the quality and performance of cement.
[0033] The role of silica fume in concrete includes: accelerating the hydration of cementitious material system, improving concrete strength, increasing density, improving concrete segregation and water seepage performance, improving impermeability and chemical corrosion resistance. In addition, silica fume can also improve the process performance of concrete, improve processability, slow down the corrosion rate of steel bars, and extend the service life of concrete.
[0034] The repair material of the present invention has the following characteristics: fast setting time, high early strength, and can be quickly opened to traffic and used; strong weather resistance, frost resistance, impermeability, and corrosion resistance; higher compressive and flexural strength, good wear resistance, micro-expansion, self-compacting, no shrinkage, and no cracking after hardening; high bonding strength and no hollowing; small color difference and ability to adjust the color of the material; convenient construction, good product fluidity, no need to collect light, high construction efficiency, and low labor cost; green and environmentally friendly, non-toxic and harmless, and free of any odor.
[0035] The repair material of the present invention is used to repair surface defects and internal damage of concrete structures, such as potholes, cracks, honeycombs, rough surfaces, peeling, hollowing, shelling, exposed steel bars, etc.; such as steel bar corrosion, concrete corrosion, etc.; repairing damaged concrete pavements and other structures without cracking, with good adhesion to the base layer, good fluidity, and high early strength. DETAILED DESCRIPTION
[0036] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the embodiments of the present application; obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments, and all other embodiments obtained by ordinary technicians in this field based on the embodiments in the present application without making creative work are within the scope of protection of the present application.
[0037] Example 1
[0038] A superfast hardening concrete repair material includes the following raw materials in parts by weight: 420 parts of high belite sulphoaluminate cement, 480 parts of fine aggregate, 2.5 parts of polycarboxylic acid water reducer, 0.8 parts of lithium carbonate accelerator, 0.4 parts of sodium sulphate retarder, 1.2 parts of polypropylene fiber, 0.7 parts of defoamer, 5 parts of masterbatch (including suspending agent), 11 parts of corrosion-resistant material, 60 parts of fly ash, 60 parts of heavy calcium powder, 10.5 parts of talcum powder, 8.5 parts of bauxite powder, 18 parts of silica fume, 17 parts of rubber powder, 45 parts of color powder, and 0.7 parts of water retaining agent (cellulose). In the present application, the corrosion-resistant material is acid-resistant powder.
[0039] The preparation method of the ultra-fast hardening concrete repair material comprises the following steps:
[0040] S1. Weigh the above raw materials and set aside;
[0041] S2. Place the raw materials in S1 in a powder mixer and mix them evenly to obtain a repair material.
[0042] The construction method of the ultra-fast hardening concrete repair material comprises the following steps:
[0043] S1. Clean the concrete surface to be repaired;
[0044] S2. Mix the above repair materials with water and mix them evenly at the construction site, then apply them on the concrete surface to be repaired;
[0045] S3. After solidification, the repair of the concrete is completed.
[0046] Example 2
[0047] An ultrafast hardening concrete repair material includes the following raw materials in parts by weight: 440 parts of high belite sulphoaluminate cement, 490 parts of fine aggregate, 3 parts of polycarboxylate water reducer, 1 part of lithium carbonate accelerator, 0.5 parts of sodium citrate retarder, 1.5 parts of steel fiber, 0.8 parts of defoamer, 5 parts of masterbatch (including suspending agent), 11.5 parts of corrosion-resistant material, 70 parts of fly ash, 70 parts of heavy calcium powder, 11 parts of talcum powder, 9 parts of bauxite powder, 20 parts of silica fume, 18 parts of rubber powder, 50 parts of color paste, and 0.8 parts of water retaining agent (cellulose). In the present application, the corrosion-resistant material is acid-resistant powder.
[0048] The preparation method of the ultra-fast hardening concrete repair material comprises the following steps:
[0049] S1. Weigh the above raw materials and set aside;
[0050] S2. Place the raw materials in S1 in a powder mixer and mix them evenly to obtain a repair material.
[0051] The construction method of the ultra-fast hardening concrete repair material comprises the following steps:
[0052] S1. Clean the concrete surface to be repaired;
[0053] S2. Mix the above repair materials with water and mix them evenly at the construction site, then apply them on the concrete surface to be repaired;
[0054] S3. After solidification, the repair of the concrete is completed.
[0055] Example 3
[0056] A superfast hardening concrete repair material includes the following raw materials in parts by weight: 460 parts of high belite sulphoaluminate cement, 500 parts of fine aggregate, 3.5 parts of polycarboxylate water reducer, 1.2 parts of lithium carbonate accelerator, 0.6 parts of tartaric acid retarder, 1 part each of polypropylene fiber and steel fiber, 0.9 parts of defoamer, 5 parts of masterbatch (including suspending agent), 12 parts of corrosion-resistant material, 80 parts of fly ash, 80 parts of heavy calcium powder, 11.5 parts of talcum powder, 9.5 parts of bauxite powder, 22 parts of silica fume, 19 parts of rubber powder, 55 parts of color powder, and 0.9 parts of water retaining agent (cellulose). In the present application, the corrosion-resistant material is acid-resistant powder.
[0057] The preparation method of the ultra-fast hardening concrete repair material comprises the following steps:
[0058] S1. Weigh the above raw materials and set aside;
[0059] S2. Place the raw materials in S1 in a powder mixer and mix them evenly to obtain a repair material.
[0060] The construction method of the ultra-fast hardening concrete repair material comprises the following steps:
[0061] S1. Clean the concrete surface to be repaired;
[0062] S2. Mix the above repair materials with water and mix them evenly at the construction site, then apply them on the concrete surface to be repaired;
[0063] S3. After solidification, the repair of the concrete is completed.
[0064] Example 4
[0065] An ultrafast hardening concrete repair material includes the following raw materials in parts by weight: 470 parts of high belite sulphoaluminate cement, 510 parts of fine aggregate, 3.8 parts of polycarboxylate water reducer, 1.4 parts of lithium carbonate accelerator, 0.8 parts of sodium nitrate retarder, 1.8 parts of steel fiber, 1 part of defoamer, 5 parts of masterbatch (including suspending agent), 12.5 parts of corrosion-resistant material, 90 parts of fly ash, 90 parts of heavy calcium powder, 11.8 parts of talcum powder, 9.8 parts of bauxite powder, 24 parts of silica fume, 19.5 parts of rubber powder, 58 parts of color paste, and 0.95 parts of water retaining agent (cellulose). In the present application, the corrosion-resistant material is acid-resistant powder.
[0066] The preparation method of the ultra-fast hardening concrete repair material comprises the following steps:
[0067] S1. Weigh the above raw materials and set aside;
[0068] S2. Place the raw materials in S1 in a powder mixer and mix them evenly to obtain a repair material.
[0069] The construction method of the ultra-fast hardening concrete repair material comprises the following steps:
[0070] S1. Clean the concrete surface to be repaired;
[0071] S2. Mix the above repair materials with water and mix them evenly at the construction site, then apply them on the concrete surface to be repaired;
[0072] S3. After solidification, the repair of the concrete is completed.
[0073] Example 5
[0074] An ultrafast hardening concrete repair material includes the following raw materials in parts by weight: 480 parts of high belite sulphoaluminate cement, 520 parts of fine aggregate, 4 parts of polycarboxylate water reducer, 1.5 parts of lithium carbonate accelerator, 1 part of sodium citrate retarder, 2 parts of polypropylene fiber, 1 part of defoamer, 5 parts of masterbatch (including suspending agent), 13 parts of corrosion-resistant material, 100 parts of fly ash, 100 parts of heavy calcium powder, 12 parts of talcum powder, 10 parts of bauxite powder, 25 parts of silica fume, 20 parts of rubber powder, 60 parts of color powder, and 1 part of water retaining agent (cellulose). In the present application, the corrosion-resistant material is acid-resistant powder.
[0075] The preparation method of the ultra-fast hardening concrete repair material comprises the following steps:
[0076] S1. Weigh the above raw materials and set aside;
[0077] S2. Place the raw materials in S1 in a powder mixer and mix them evenly to obtain a repair material.
[0078] The construction method of the ultra-fast hardening concrete repair material comprises the following steps:
[0079] S1. Clean the concrete surface to be repaired;
[0080] S2. Mix the above repair materials with water and mix them evenly at the construction site, then apply them on the concrete surface to be repaired;
[0081] S3. After solidification, the repair of the concrete is completed.
[0082] Performance indicators of Examples 1-5
[0083] 1. Setting time: The initial setting time is within 1 hour, and the final setting time is within 3 hours, which can achieve rapid construction and traffic.
[0084] 2. Early strength: 24-hour compressive strength reaches more than 60MPa, flexural strength reaches more than 15MPa, and early strength is high.
[0085] 3. Weather resistance:
[0086] Frost resistance: After multiple freeze-thaw cycles, the strength loss is less than 15%.
[0087] Impermeability: The impermeability grade reaches P8 or above.
[0088] Corrosion resistance: After immersion in acid, alkali, salt and other media, the strength loss is less than 10%.
[0089] 4. Compression and flexural strength: The compressive strength after 28 days reaches more than 70MPa, and the flexural strength reaches more than 20MPa.
[0090] 5. Convenience of construction: good fluidity, no need to collect light, high construction efficiency and low labor cost.
[0091] Test results
[0092]
[0093]
[0094] Comparative Example 1
[0095] The raw materials of a concrete repair material are as follows: 450 parts of ordinary Portland cement, 500 parts of fine aggregate, 3 parts of water reducing agent (lignin sulfonate), 1 part of accelerator (calcium chloride), 0.5 parts of retarder (sodium gluconate), 1.5 parts of fiber (polypropylene fiber), 0.8 parts of defoaming agent, 10 parts of corrosion-resistant material, 70 parts of fly ash, 70 parts of heavy calcium powder, 11 parts of talcum powder, 9 parts of bauxite powder, 20 parts of silica fume, 18 parts of rubber powder, 50 parts of color powder and 0.8 parts of water retaining agent (cellulose).
[0096] Performance comparison:
[0097] Setting time: the initial setting time is about 2 hours, and the final setting time is about 5 hours, which is obviously longer than that of the embodiment.
[0098] Early strength: The 24-hour compressive strength is only about 10 MPa, and the flexural strength is about 2 MPa, which is much lower than that of the embodiment.
[0099] Weather resistance: The frost resistance, impermeability and corrosion resistance are not as good as those in the examples.
[0100] Compression and flexural strength: The 28-day compressive strength is about 30 MPa, and the flexural strength is about 4 MPa, which are lower than those in the embodiment.
[0101] Construction convenience: poor fluidity, need to be lightened, low construction efficiency and high labor cost.
[0102] Comparative Example 2
[0103] The raw materials of a concrete repair material are as follows: 440 parts of high-belite sulphoaluminate cement, 490 parts of fine aggregate, 3 parts of polycarboxylic acid water reducer, 1 part of lithium carbonate accelerator, no retarder, 1.5 parts of fiber (steel fiber), 0.8 parts of defoamer, 5 parts of masterbatch (including suspending agent), 11.5 parts of corrosion-resistant material, 70 parts of fly ash, 70 parts of heavy calcium powder, 11 parts of talcum powder, 9 parts of bauxite powder, 20 parts of silica fume, 18 parts of rubber powder, 50 parts of color paste and 0.8 part of water retaining agent (cellulose).
[0104] Performance comparison:
[0105] Setting time: Due to the absence of retarder, the setting time is too fast, which is not conducive to construction operations.
[0106] Early strength: Similar to that of Example 15, but due to rapid setting, the construction quality may be difficult to control.
[0107] The weather resistance, compressive and flexural strength have no obvious advantages over the fifteenth embodiment, but the convenience of construction is affected.
[0108] The repair material of the present invention has the following characteristics: fast setting time, high early strength, and can be quickly opened to traffic and used; strong weather resistance, frost resistance, impermeability, and corrosion resistance; higher compressive and flexural strength, good wear resistance, micro-expansion, self-compacting, no shrinkage, and no cracking after hardening; high bonding strength and no hollowing; small color difference and ability to adjust the color of the material; convenient construction, good product fluidity, no need to collect light, high construction efficiency, and low labor cost; green and environmentally friendly, non-toxic and harmless, and free of any odor.
[0109] The repair material of the present invention is used to repair surface defects and internal damage of concrete structures, such as potholes, cracks, honeycombs, rough surfaces, peeling, hollowing, shelling, exposed steel bars, etc.; such as steel bar corrosion, concrete corrosion, etc.; repairing damaged concrete pavements and other structures without cracking, with good adhesion to the base layer, good fluidity, and high early strength.
[0110] The above is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. An ultra-fast hardening concrete repair material, characterized in that: It includes the following raw materials in parts by weight: 400-480 parts of high-belite sulphoaluminate cement, 470-520 parts of fine aggregate, 2-4 parts of water reducer, 0.3-1.5 parts of accelerator, 0.3-1.0 parts of retarder, 1-2 parts of fiber, 0.5-1.0 parts of defoamer, 4-6 parts of masterbatch, 10-13 parts of corrosion-resistant material, 15-20 parts of adhesive, 40-60 parts of color powder or color paste, 0.5-1.0 parts of water retaining agent, and the rest are admixtures; The admixture includes one or more of fly ash, heavy calcium powder, talcum powder, bauxite powder, and silica ash, wherein the fly ash is 50-100 parts, the heavy calcium powder is 50-100 parts, the talcum powder is 10-12 parts, the bauxite powder is 8-10 parts, and the silica ash is 15-25 parts.
2. The ultra-fast hardening concrete repair material according to claim 1, characterized in that: The water reducing agent is polycarboxylic acid.
3. The ultra-fast hardening concrete repair material according to claim 1, characterized in that: The coagulant is lithium carbonate.
4. The ultra-fast hardening concrete repair material according to claim 1, characterized in that: The retarder includes one or more of sodium tartrate, sodium citrate and tartaric acid.
5. The ultra-fast hardening concrete repair material according to claim 1, characterized in that: The fibers are polypropylene fibers and / or steel fibers.
6. The ultra-fast hardening concrete repair material according to claim 1, characterized in that: The corrosion-resistant material includes acid-resistant powder.
7. The ultra-fast hardening concrete repair material according to claim 1, characterized in that: The adhesive is rubber powder.
8. The ultra-fast hardening concrete repair material according to claim 1, characterized in that: The water retaining agent is cellulose.
9. A method for preparing an ultra-fast hardening concrete repair material according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Weigh the above raw materials and set aside; S2. Place the raw materials in S1 in a powder mixer and mix them evenly to obtain a repair material.
10. A construction method of an ultra-fast hardening concrete repair material according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Clean the concrete surface to be repaired; S2. Mix the above repair materials with water and mix them evenly at the construction site, then apply them on the concrete surface to be repaired; S3. After solidification, the repair of the concrete is completed.